2022
DOI: 10.3389/fimmu.2022.981251
|View full text |Cite
|
Sign up to set email alerts
|

Development of a screening score for Hemophagocytic Lymphohistiocytosis among pediatric patients with acute infection of Epstein-Barr virus

Abstract: Background and aimsDeciding when to suspect hemophagocytic lymphohistiocytosis (HLH) and perform diagnostic tests in patients with acute infection of Epstein-Barr virus (EBV) is challenging, given the high prevalence of EBV infection, the life-threatening risk of EBV-HLH, the relatively low incidence of EBV-HLH, and the wide spectrum of disease presentations. The aim of this study was to develop an EBV-HLH screening model for pediatric patients diagnosed with acute infection of EBV.MethodsAn inpatient cohort w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Most current prediction model were tailored to adult patients with HLH [16], or pediatric patients with speci c etiologies, such as EBV-HLH [17]. Comparing adult patients with HLH, pediatric patients experience higher morbidity and early mortality: A recent long-term retrospective study from China involving adult HLH patients reported the 30-day mortality rate of 16.35% between 2013 and 2018 [18]; in our study, 20% of the pediatric HLH patients died within 28 days since diagnosis, as approximately consistent with results from previous studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most current prediction model were tailored to adult patients with HLH [16], or pediatric patients with speci c etiologies, such as EBV-HLH [17]. Comparing adult patients with HLH, pediatric patients experience higher morbidity and early mortality: A recent long-term retrospective study from China involving adult HLH patients reported the 30-day mortality rate of 16.35% between 2013 and 2018 [18]; in our study, 20% of the pediatric HLH patients died within 28 days since diagnosis, as approximately consistent with results from previous studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study indicated that ferritin had good specificity and sensitivity in separating the two diseases at an early stage, some infants with HLH did not exhibit typical symptoms of elevated ferritin at that time; therefore, a comprehensive diagnosis model with multiple indicators is required. Li et al developed an EBV-HLH score with five parameters, including hemoglobin, platelet, neutrophil, albumin, and LDH, which has a sensitivity of 89.2% and a specificity of 89.5%, to help identify EBV patients that need additional HLH screening [ 12 ]. Smits et al discovered a minimal parameter set consisting phagocytosis, splenomegaly, cytopenia, increased ferritin, and increased triglycerides that can predict HLH with a sensitivity of 95% and a specificity of 94% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our team has used a cytokine profile as a supplementary instrument for rapidly evaluating HLH [ 10 , 11 ], and it is essential to discover other clinical or laboratory markers that aid in the early identification of HLH in patients with childhood EBV-IM in addition to the cytokine pattern. Li et al and Smits et al have developed predict models to early identify HLH patients from those with acute EBV-infection or suspected HLH, which include clinical, biologic, and cytologic variables but without cytokine profile [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%